2022
DOI: 10.1101/2022.09.20.508669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Choice seeking is motivated by the intrinsic need for personal control

Abstract: When deciding between options that do or do not lead to future choices, humans often choose to choose. We studied choice seeking by asking subjects to decide between a choice opportunity or performing a computer-selected action. Subjects preferred choice when these options were equally rewarded, even deterministically, and were willing to trade extrinsic rewards for the opportunity to choose. We explained individual variability in choice seeking using reinforcement learning models incorporating risk sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…We observed that Parkinson’s disease patients OFF DBS were indifferent between the free and forced options, while ON DBS they increased their free choice preference to a level close to that observed in healthy humans using similar experimental designs 15,37 . This improvement in choice preference was associated with increased connectivity between medial frontal cortical (MFC) and the VATs constructed with individual parameters of each patient side by side.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…We observed that Parkinson’s disease patients OFF DBS were indifferent between the free and forced options, while ON DBS they increased their free choice preference to a level close to that observed in healthy humans using similar experimental designs 15,37 . This improvement in choice preference was associated with increased connectivity between medial frontal cortical (MFC) and the VATs constructed with individual parameters of each patient side by side.…”
Section: Discussionsupporting
confidence: 65%
“…To further investigate the role of dopamine in intrinsic motivation, we asked whether dopamine replacement therapy modulates choice preference in a second group of Parkinson's disease patients. We found that on average patients in the DOPA group preferred choice at a similar level to healthy humans 15,37 , independent of acute levodopa treatment. However, chronic medication type can influence behavioral (dys)functions in distinct manners 3,78 .…”
Section: Chronic Low Doses Of Levodopa Impair Free Choice Preferencementioning
confidence: 75%
See 3 more Smart Citations